2012
DOI: 10.1111/ppe.12004
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Antiepileptic Drugs among Pregnant Women in the US, 2001–2007: A Medication Exposure in Pregnancy Risk Evaluation Program Study

Abstract: Background-Little is known about the extent of antiepileptic drug (AED) use in pregnancy, particularly for newer agents. Our objective was to assess whether AED use has increased among pregnant women in the U.S., 2001-2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 38 publications
6
52
3
Order By: Relevance
“…They found that 0.9% received benzodiazepines at any time in pregnancy while 0.2% received valproic acid derivatives. 40 Of those who were dispensed an old anticonvulsant mood stabiliser 4024 out of 9001 (45%) had an indication of psychiatric disorder, while 2115 out of 3515 (60%) of those dispensed new anticonvulsant mood stabilisers had an indication of psychiatric disorder. Only between 21% and 25% had an indication of epilepsy.…”
Section: Psychotropic Medication Prescribed Before During and After mentioning
confidence: 99%
See 4 more Smart Citations
“…They found that 0.9% received benzodiazepines at any time in pregnancy while 0.2% received valproic acid derivatives. 40 Of those who were dispensed an old anticonvulsant mood stabiliser 4024 out of 9001 (45%) had an indication of psychiatric disorder, while 2115 out of 3515 (60%) of those dispensed new anticonvulsant mood stabilisers had an indication of psychiatric disorder. Only between 21% and 25% had an indication of epilepsy.…”
Section: Psychotropic Medication Prescribed Before During and After mentioning
confidence: 99%
“…7 The utilisation of anticonvulsant mood stabilisers was examined in another US study also based on pharmacy dispensing data from nearly 600,000 pregnancies. 40 This study included benzodiazepines as one of the 'older' anticonvulsant mood stabilisers and the prevalence estimates were primarily driven by the dispensing of these drugs. They found that 0.9% received benzodiazepines at any time in pregnancy while 0.2% received valproic acid derivatives.…”
Section: Psychotropic Medication Prescribed Before During and After mentioning
confidence: 99%
See 3 more Smart Citations